Biotype and host relatedness influence the composition of bacterial microbiomes in Schizaphis graminum aphids - Crane, Yan M.; Crane, Charles F.; Webb, Christian; Schemerhorn, Brandon J. (Frontiers in Microbiology, 2025)
IntroductionThe microbiome of greenbug aphid (Schizaphis graminum (Rondani)) was investigated in regard to greenbug biotype, collection date, host species, and host cultivar.MethodsDNA samples were collected from biotypes E and K feeding on 17 cultivars belonging to five host plant species, namely wheat, barley, rye, sorghum, and the goatgrass Aegilops triuncialis. Samples were taken immediately before infestation and two, four, and eight days thereafter. The V5-V7 hypervariable region of 16S rDNA was PCR amplified, Illumina sequenced, and aligned to a curated database of bacterial 16S rDNA sequences.Results and discussionThe almost universal intracellular endosymbiont of aphids, Buchnera aphidicola, comprised 78.24 to 99.99% of the read counts among samples, largely because of its high copy number of genomes per bacteroid. Abundant non-Buchnera genera included Pseudomonas, Rhodanobacter, Massilia, and Enterobacter. Read counts of eight of 78 examined genera were more than 90% restricted to a single replicate of a single treatment. Shannon entropy was highest in biotype K and on the barley host, but it did not vary significantly among dates post infestation. Unweighted UniFrac distances most significantly varied with biotype, host plant species, infestation time, and almost all of their interactions. Weighted UniFrac and Jaccard distances varied less significantly. By counts of differentially populated genera, the factors biotype, host plant species, infestation time, and host plant resistance genes to greenbug, were consecutively less important. Functional analysis with PICRUSt2 illustrated a diminution of respiratory electron transport and long-chain fatty acids in the Buchnera endosymbiont, reflecting adaptation to an intracellular environment.